XYLOPHONES IN THE SUDAN (International Library of African Music, 1970)
Interesting details of the construction of a Rongo xylophone in the Sudan has been sent us by Mr. David Evans who, for many years, was a member of the Sudan Political Service. The extract he sends is taken from the Sudan Notes and Records, Vol. XXVIII, 1947 (pp. 179-181) and was written by Faustino Roro Kamitin, who is a member of the Gbaya tribe and son of the hereditary maker of the rongo for his clan.
Keywords: Xylophone; Musical instruments; African Music; Sudan; Xylophone (Instrument)